Influence of the methodology safety based on behavior in the prevention and reduction of the number of accidents in CAME Contractors and General Services S.A. – Antamina Project – Period 2014 - Cajia Lucio, Tito (2019)
The main objective of this study is to determine the influence of the methodology Safety Based on Behavior (SBC) in the prevention and reduction of the number of accidents in the company CAME Contratistas y Servicios Generales S.A For this purposethe theoretical, conceptual and technical bases of Safety Based on Behavior (SBC) are presented, aimed at identifying and changing risk behaviors of workers through safe behaviors from the generation of action plans, seeking to contribute in the reduction of accidents and incidents and the improvement of security management. The research carried out was of the semi-experimental type, with a sample of 120 people, where a simple, proportional and permanent random sample was generated, using the techniques of field data collection through the use of SBC primers with security observers. And the one of cabinet entering the information in the software SBC to determine the behaviors. This process and behavior management allowed to reduce the number of accidents and incidents, which were characterized when comparing the statistical data of the years 2012 and 2013 with respect to 2014, showing a significant improvement in safety performance of the company. After all this process, it can be affirmed that the SBC methodology does have a positive influence on the prevention and reduction of accidents.